Strategi Adiwana Hotels & Resorts Dalam Mempertahankan Eksistensinya Pada Masa Pandemi Covid-19 Dan Era New Normal - Anak Agung Istri Ratna Sari Wulan (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
The coronavirus outbreak began in China to spread to the rest of the world making the world tourism industry including Indonesia also sluggish. The mobilization of people is very limited because of the government regulations of each country that prohibit its residents from traveling out of the city. Limited travel activities cause the occupancy rate of rooms in accommodation facilities such as hotels, villas, homestays, quiet vacation homes and even many empty ones. The impact on the closure of hotels, villas and other types of accommodation and sold at low prices.The formulation of this research problem is what strategies Adiwana Hotels & Resorts implements in maintaining its existence during the Covid-19 pandemic and the new normal era and how Adiwana hotels & resorts strategy is implemented in maintaining its existence during the Covid-19 pandemic and the new normal era.This research method uses qualitative methods with data collection through observation techniques, interviews and questionnaire deployments. The theoretical studies used are hotel theory, villa theory, existence theory, strategy theory, Covid-19 pandemic theory and new normal era theory. The results of this study showed varying results.